Pengaruh Harga dan Kualitas Produk terhadap Loyalitas Distributor Keripik Singkong - Nasyirudin, Muhammad; Andari, Bina; Trioko, Sunan; Wijaya, Hendra Agung (STKIP PGRI SITUBONDO, 2024)
The agricultural sector is the most important sector both in the long term of economic development and for short term economic recovery. Now is a good time to explore thoughts on reorienting agricultural development policies. The agricultural development policy is directed so that agriculture becomes a resilient sector, in the short term able to face the economic crisis, and in the long term able to face globalization with a sustainable agricultural system, in a democratic economic system and in a decentralized government. This research aims to analyze whether price and product quality influence the loyalty of cassava chips distributors. Distributor loyalty is a concern for companies if the product wants to continue to be on the market. The population in this study were cassava chips distributors. The samples taken were 78 respondents. Analysis of the data used in this research was assisted by SPSS version 25. Using a survey research method with a quantitative research type. The results show that price has an effect on distributor loyalty. Product quality has a partial and simultaneous effect on distributor loyalty. Thus the higher the price and quality of the product, the higher the loyalty of the contributor. Thus, UD trigoferous must improve product quality such as increasing product durability. So that the product can be stored longer.